Field-deployable multiplex detection method of SARS-CoV-2 and influenza virus using loop-mediated isothermal amplification and DNA chromatography - Hayashida, Kyoko; Garcia, Alejandro; Moonga, Lavel Chinyama; Sugi, Tatsuki; Takuya, Kodera; Kawase, Mitsuo; Kodama, Fumihiro; Nagasaka, Atsushi; Ishiguro, Nobuhisa; Takada, Ayato; Kajihara, Masahiro; Nao, Naganori; et al. (PloS one, 2023)
A novel multiplex loop-mediated isothermal amplification (LAMP) method combined with DNA chromatography was developed for the simultaneous detection of three important respiratory disease-causing viruses: severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza A virus, and influenza B virus. Amplification was performed at a constant temperature, and a positive result was confirmed by a visible colored band. An in-house drying protocol with trehalose was used to prepare the dried format multiplex LAMP test. Using this dried multiplex LAMP test, the analytical sensitivity was determined to be 100 copies for each viral target and 100–1000 copies for the simultaneous detection of mixed targets. The multiplex LAMP system was validated using clinical COVID-19 specimens and compared with the real-time qRT-PCR method as a reference test. The determined sensitivity of the multiplex LAMP system for SARS-CoV-2 was 71% (95% CI: 0.62–0.79) for cycle threshold (Ct) ≤ 35 samples and 61% (95% CI: 0.53–0.69) for Ct ≤40 samples. The specificity was 99% (95%CI: 0.92–1.00) for Ct ≤35 samples and 100% (95%CI: 0.92–1.00) for the Ct ≤40 samples. The developed simple, rapid, low-cost, and laboratory-free multiplex LAMP system for the two major important respiratory viral diseases, COVID-19 and influenza, is a promising field-deployable diagnosis tool for the possible future ‘twindemic, ‘ especially in resource-limited settings.